Occupational Safety Analysis Using the Hazard Identification And Risk Assessment Control (HIRAC) Method at Pt. Sucofindo Duri Year 2022: Analisis Keselamatan Kerja Dengan Menggunakan Metode Hazard Identification And Risk Assessment Control (HIRAC) Di Pt. Sucofindo Duri Tahun 2022 - Tasya Mayangsari; Reno Renaldi; Alhidayati Alhidayati; Novita Lusiana; Makomulamin Makomulamin (Badnur Medisa Group, 2022)
Hazard Identification and Risk Assessment and Control (HIRAC) is a method of identifying work accidents with risk assessment as one of the important points for implementing the Occupational Health and Safety Management System (SMK3). risk analysis that depending on the type of work, if the job is radiography, it is called high because of the dangers of radiation. PT.Sucofindo has conducted a risk analysis and conducted a medical check-up, they must understand the work in the field. Occupational Health and Safety (OHS) is in the interest of employers, workers and governments around the world. According to ILO estimates, every year around the world 2 million people die from work-related problems. The purpose of the study was to analyze work safety data using the Hazard Identification and Risk Assessment Control (HIRAC) method at PT.Sucofindo Duri in 2022. The research design was qualitative. There were 3 informants namely, Company Leaders, HSE Officers, and Safety Officers. The results of the research PT, Sucofindo have conducted research, and have SOP and JSA, already know the potential hazards and risk actions in the field. Research suggestions for leaders must control every job so that accidents do not occur in the field, For HSE Officers to identify and map the potential hazards that occur in the work environment.